High‐Throughput Computational Evaluation of Low Symmetry Pd2L4 Cages to Aid in System Design. (11th August 2021) - Tarzia, Andrew; Lewis, James E. M.; Jelfs, Kim E.
Abstract: Unsymmetrical ditopic ligands can self‐assemble into reduced‐symmetry Pd2 L4 metallo‐cages with anisotropic cavities, with implications for high specificity and affinity guest‐binding. Mixtures of cage isomers can form, however, resulting in undesirable system heterogeneity. It is paramount to be able to design components that preferentially form a single isomer. Previous data suggested that computational methods could predict with reasonable accuracy whether unsymmetrical ligands would preferentially self‐assemble into single cage isomers under constraints of geometrical mismatch. We successfully apply a collaborative computational and experimental workflow to mitigate costly trial‐and‐error synthetic approaches. Our rapid computational workflow constructs unsymmetrical ligands and their Pd2 L4 cage isomers, ranking the likelihood for exclusively forming cis ‐Pd2 L4 assemblies. From this narrowed search space, we successfully synthesised four new, low‐symmetry, cis ‐Pd2 L4 cages. Abstract : Towards the development of sophisticated metal‐organic hosts, low‐symmetry metallo‐supramolecular cages assembled from unsymmetrical ligands are of emerging interest. Designing systems to avoid forming isomeric mixtures, however, is challenging. We report the use of a rapid computational workflow to predict self‐assembly outcomes, informing experimental decisions and optimising synthetic realisation of low‐symmetry, cis ‐Pd2 L4 cages.